Exploring complementary medicine practitioners' attitudes towards the use of an immunization decision aid, and its potential acceptability for use with clients to reduce vaccine related decisional conflict. Issue 2 (1st February 2021) - Frawley, Jane E.; McKenzie, Kirsty; Forssman, Bradley L.; Sullivan, Elizabeth; Wiley, Kerrie
ABSTRACT: While Australia boasts a high immunization rate, geographical pockets of low uptake still challenge herd immunity on a community level. For some parents, concerns about immunization lead to distrust of conventional sources of vaccine information and complementary medicine (CM) practitioners may be more readily trusted as a source of information about vaccines. Decision aids are common educational resources that are developed to support informed decision making. We interviewed CM practitioners to explore their attitudes to immunization decision aids in general and the acceptability of recommending this resource to parents with concerns or questions about immunization. While some practitioners felt that it might be biased towards immunizations, all said that they would recommend the resource to parents. CM practitioners are a trusted source of information, including immunization advice for some parents. CM practitioners were generally supportive of decision aids as a tool they could use in their practice to help parents with immunization questions, where a premium is often placed on patient choice.